(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The results of hybridization Prunus brigantiaca x Prunus cerasifera Ehrh. are elucidated. In the first generation hybrids show much later flowering period and ripening of fruits in comparison with other cultivars. In the second generation hybrids have also higher content of dry substances, pectines and anthocyanes in its fruits.